Global bioethics and human rights : contemporary perspectives - Teays, Wanda; Renteln, Alison Dundes (Lanham Rowman and Littlefield, 2020)
"The ethical issues we face in healthcare, justice, and human rights extend beyond national boundaries-they are global and cross-cultural in scope. The second edition of this interdisciplinary and international collection features new essays on gender identity, vaccines, stem cells, bioterror, and other pressing contemporary concerns"--
Includes bibliographical references.
Keywords: Bioethics; Human rights